ALDH2 Expression, Alcohol Intake and Semen Parameters among East Asian Men. Issue 2 (28th August 2022) - Greenberg, Daniel R.; Bhambhvani, Hriday P.; Basran, Satvir S.; Salazar, Brett P.; Rios, Luis Carl; Li, Sin-Jin; Chen, Che-Hong; Mochly-Rosen, Daria; Eisenberg, Michael L.
Abstract : Purpose: Inactivating mutations in mitochondrial aldehyde dehydrogenase 2 (ALDH2) are highly prevalent. The most common variant allele, ALDH2*2, is present in 40%–50% of East Asians, and causes acetaldehyde accumulation, flushing and tachycardia after alcohol intake. The relationship between alcohol intake and ALDH2 genotype on semen parameters remains unknown. Materials and Methods: We conducted a cross-sectional study to determine the association between ALDH2 genotype, alcohol consumption and semen parameters among East Asian men. Volunteers completed a survey and submitted a semen sample for analysis. Participants were genotyped to determine ALDH2 status ( ALDH2*1/*1, ALDH2*1/*2, ALDH2*2/*2 ), and immunohistochemical staining was used to determine protein expression of ALDH2 in spermatozoa. Results: Of 112 men 45 (40.2%) were ALDH2*2 carriers. Among ALDH2*2 carriers, alcohol consumption was associated with significantly lower total sperm motility (median 20% [interquartile range 11%–42%] vs 43% [IQR 31%–57%], p=0.005) and progressive sperm motility (19% [IQR 11%–37%] vs 36% [IQR 25%–53%], p=0.008). Among alcohol consumers, ALDH2*2 carriers had significantly lower total sperm motility (20% [IQR 11%––42%] vs 41% [IQR 19%–57%], p=0.02), progressive sperm motility (19% [IQR 11%–37%] vs 37% [IQR 17%–50%], p=0.02) and total motile sperm count (28 million [M; IQR 9–79M] vs 71M [IQR 23–150M], p=0.05) compared to ALDH2*1/*1 individuals. Secondly, ALDH2 expression in human spermatozoa was significantly lower in ALDH2*2 carriers ( ALDH2*1/*1 vs ALDH2*1/*2, p=0.01; ALDH2*1/*1 vs ALDH2*2/*2, p <0.001). Conclusions: Our findings suggest genotyping ALDH2, coupled with alcohol cessation counseling, may improve semen parameters among men.